2022
DOI: 10.1002/casp.2639
|View full text |Cite
|
Sign up to set email alerts
|

Belief, attitude and critical understanding. A systematic review of social justice in Service‐Learning experiences

Abstract: This systematic review examined the role of Service-Learning experiences promoted by higher education institutions to strengthen the achievement of social justice outcomes among youth. We screened and coded studies following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Of the 555 articles found in the database search, 47 peer-reviewed studies were included in the final sample. Social justice construct, together with research location, participants, target community and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 119 publications
0
4
0
1
Order By: Relevance
“…Another systematic review of 47 studies also reported that service-learning is effective in fostering signi cant improvement in students' social justice beliefs, stimulating signi cant changes in their attitudes towards developing altruistic behaviours and their commitment to social justice, and increasing their critical understanding by sparking questioning processes related to personal assumptions of inequalities [23]. Based on a recent meta-synthesis, it is recommended that the core medical school curriculum should include mandatory training to enable students to identify and address adverse social factors that are medically relevant [24]. The participants in our study recommended increasing the availability and accessibility of educational programs in the eld of social accountability during medical and pharmacy education.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review of 47 studies also reported that service-learning is effective in fostering signi cant improvement in students' social justice beliefs, stimulating signi cant changes in their attitudes towards developing altruistic behaviours and their commitment to social justice, and increasing their critical understanding by sparking questioning processes related to personal assumptions of inequalities [23]. Based on a recent meta-synthesis, it is recommended that the core medical school curriculum should include mandatory training to enable students to identify and address adverse social factors that are medically relevant [24]. The participants in our study recommended increasing the availability and accessibility of educational programs in the eld of social accountability during medical and pharmacy education.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The objective of educational programs, such as SOLID'AIRS, is to raise awareness of the realities of other healthcare systems and to train professionals capable of nding a useful place for themselves in a complex healthcare system. Therefore, it is critical to assess the impact of these study programs on students and the social determinants of health [9,[23][24][25]. Regarding the impact of the SOLID'AIRS program, students reported professional bene ts, including improved group work skills.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Profile membership was associated with racial identity, racial socialization, and experiences of racial stress. Compare and Albanesi (2023) present a systematic review of service-learning in higher education settings as a way to foster social justice outcomes. They reviewed 47 papers documenting that service-learning experiences promoted social justice beliefs, fostered the development of altruistic behaviours and commitment to social justice, and shaped participants' critical understanding of processes such as injustices.…”
Section: Palmer Et Al (mentioning
confidence: 99%
“…CEL also has the potential to effectively enhance students’ understanding of migrants’ experiences and reinforce students’ appreciation for education and career readiness (Costigan et al, 2022; Wickline et al, 2021). Research shows that service learning is positively linked to students’ interest, engagement, program attitudes, empathy, and intercultural competence (Cadenas et al, 2022; Celio et al, 2011; Compare & Albanesi, 2023; Crone, 2023). Intercultural competence involves attitudes, knowledge, and skills supporting effective interaction in diverse cultural contexts (Deardorff & Arasaratnam-Smith, 2017).…”
Section: Teaching Approach and Learning Activitiesmentioning
confidence: 99%